Le profil immunohistochimique d’HER2, des récepteurs hormonaux et de Ki67 du cancer du sein chez la femme âgée de moins de 40ans - KHALDI, SOUMIA (My University, 2021)
Breast cancer (SC) is the most common malignant disease in women, but it accounts for only 7% of women under 40 years of age. This comparative study carried out on 50 patients aged less than or equal to 40 years, and 50 patients aged over 40 with CS. The objective of this study is to evaluate the immuno-histochemical profile via immunostaining HER2, ER, PR, and Ki67 of 50 young patients and a set of comparative epidemiological, histo-prognostic and clinical parameters. With that of elderly patients to show if the last molecular classification is identical between the two age groups, but above all, which is the predominant subtype that will reflect tumor aggressiveness? Histological examination revealed that no specific breast carcinoma and SBR II were the most common in both populations. The results of IHC reveal that HER2 is over expressed in 30% young patients versus 16% in elderly patients. The status of hormone receptors is negative in 36% in young patients, while 10% in elderly patients. Ki67 was high in 72% of young cases and 56% in old cases. For the young cohort, the predominant phenotypes are luminal B (54%) followed by triple negative (28%) and HER2 like (10%), and for the older cohort luminal A is slightly predominant (48%), followed by luminal B (42%). These results confirm that the more advanced forms and poorer prognosis of CS present in young patients than older ones.
Keywords: Breast cancer, immune-histochemistry, HER2, ER, PR, Ki67.